Treatment of Secondary Mitral Regurgitation in Heart Failure: A Shifting Paradigm in the Wake of the COAPT Trial - Kelly H Schlendorf; Jared O’Leary; JoAnn Lindenfeld (US Cardiology Review)
Secondary mitral regurgitation (MR) is common in patients with left heart dysfunction and it is associated with poor outcomes. Findings from the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation (COAPT) trial, published in 2018, suggest that in a subset of people with heart failure with secondary MR that persists despite optimization of guideline-directed medical therapies, there is now a role for percutaneous mitral valve repair using the MitraClip device. Defining which patients are most likely to benefit from MitraClip, and when, requires both a multidisciplinary approach centered on heart failure, as well as a recognition of the need for further research in this area.